IMD World Competitiveness Rankings - Patrick Condon; Linda Kane (National Competitiveness and Productivity Council (NCPC), 2021)
Ireland is ranked 13th out of 64 economies in the IMD's World Competitiveness Yearbook, slipping one place from 2020. Amongst the euro area countries, Ireland is ranked the 4th most competitive, a decrease of two places since last year. Ireland improved its ranking in one of the four major competitiveness pillars, Infrastructure, while the Government Efficiency pillar remained unchanged. Ireland's ranking in the Economic Performance and Business Efficiency pillars deteriorated in 2021.
Keywords: 330